Testing client-side applications with Django - Lavin, Mark (O'Reilly Media, 2015)
"You've built a fantastic REST API and client-side application to consume it. With all your focus on separating the client and server you missed on a critical piece: how do you test it? During the session we'll examine a simple REST API with Django connected to a single page application built with Backbone. We'll look at some of the tools available test the application with both Javascript unittests and integration tests written in Python. We'll also look at how to organize them in a sane way for your project workflow.If you're familiar with Python/Django but unfamiliar with Javascript frameworks, you'll get some practical examples of how to get started using them. If you're comfortable with Backbone but never written any tests for it, you'll have a good place to start."--Resource description page.